ALCOHOL OXIDATION CATALYST, METHOD OF MANUFACTURING THE SAME, AND FUEL CELL USING THE ALCOHOL OXIDATION CATALYST - SUN GONG QUAN; CHANG HYUK; CAO LEI; ZHU MING YUAN; PAK CHAN-HO (2010)
An ethanol oxidation catalyst including a Pt/Ru alloy and tin(II) oxide or tin(IV) oxide, a method of manufacturing the same, an electrode for a fuel cell including the ethanol oxidation catalyst, and a fuel cell having excellent power generation efficiency using the electrode.